1999
DOI: 10.1111/0023-8333.49.s1.8
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Accent, Comprehensibility, and Intelligibility in the Speech of Second Language Learners

Abstract: One of the chief goals of most second language learners is to be understood in their second language by a wide range of interlocutors in a variety of contexts. Although a nonnative accent can sometimes interfere with this goal, prior to the publication of this study, second language researchers and teachers alike were aware that an accent itself does not necessarily act as a communicative barrier. Nonetheless, there had been very little empirical investigation of how the presence of a nonnative accent affects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
662
10
43

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 524 publications
(776 citation statements)
references
References 30 publications
39
662
10
43
Order By: Relevance
“…Overall, the consistency among raters is satisfactory. This is in line with the results reported by Derwing and Munro (1997) and Munro and Derwing (1995), who have also reported that untrained listeners produce highly reliable ratings.…”
Section: Inter-rater Reliabilitysupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, the consistency among raters is satisfactory. This is in line with the results reported by Derwing and Munro (1997) and Munro and Derwing (1995), who have also reported that untrained listeners produce highly reliable ratings.…”
Section: Inter-rater Reliabilitysupporting
confidence: 92%
“…This paper examines the contribution of one possible factor to speech comprehensibility (hereafter, comprehensibility) differences, that of phonological awareness. By comprehensibility, we follow Munro and Derwing (1995), who describe comprehensibility as perceived ease of understanding. Like other metalinguistic abilities, phonological awareness is a construct, which is measured by how well learners can focus on the structure of the L2 system, in this case, the phonology.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the factors discussed above, individual variances in gender (Reid, 1987;Powell and Baters, 1985;Kaylani, 1996;Oxford, Nyikos and Ehrman, 1988;Oxford, 1993), motivations (Gardner, 1985;Taylor, 1974;Lenneberg, 1967;MacNamara, 1973), language learning strategies (Ellis, 1985), cognitive abilities (Skehan, 1998), intelligibilities (Munro and Derwing, 1995) and so on, may also lead to language learners' differences in L2 speech perception and/or production performance. Moreover, language learners were reported to vary significantly in terms of lip-reading skills (Demores, Bernstein, and DeHaven 1996), the degree of sensitivity to visual cues (Sennema et al, 2003), as well as the ability to integrate auditory and visual information in speech perception (Grant and Seitz, 1998).…”
Section: Factors Affecting L2 Speech Perceptionmentioning
confidence: 99%
“…Second language learners often show severe problems in learning phonetic segmental features of speech sounds as well as prosodic features of target languages since learning is influenced by the phonetic segmental and prosodic knowledge concerning their native language [1,2]. Since the vocabulary and the grammar of a foreign language can be acquired by using mainly cognitive learning strategies, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting L2 foreign accent is easily detectable for speakers which are familiar with the target language (e.g. native speakers of the target language), while second language learners often are not even aware of their phonetic faults with respect to L2 [1,2].…”
Section: Introductionmentioning
confidence: 99%